Spontaneous remission of a solitary intraspinal synovial cyst of the lumbar spine - Maezawa, Y. (Springer-Verlag, 2000)
We report on a 15-year-old boy in whom a spontaneous remission of a symptomatic synovial cyst, possibly emanating from the L4-5 facet joint, was noted. The medical history suggested that sport-related overactivity and/or minor trauma was the underlying cause. Conservative treatment for several months may be one treatment option if the cyst wall is not calcified and the symptoms and signs related to radiculopathy show a gradual decrease.